Faktor-faktor yang Melatarbelakangi Kejadian Partus Lama pada Ibu Bersalin di RSUD dr. R. Koesma Tuban - Umu Qonitul; Siti Nur Fadilah (Jurnal Kesehatan dr. Soebandi, 2019)
Causes of maternal death 90% caused by bleeding, toxemia gravidarum, infection, old partus and complications abortus. This death is most prevalent in the circumstances surrounding the actual labor can be prevented, From the data above is known that one of the causes of AKI by old labor. The purpose of this study to determine the factors the incidence of old partus in maternity mothers in RSUD Dr. R. Koesma Tuban. The type of research conducted is descriptive. Population is all maternity mothers with old partus in RSUD Dr. R. Koesma Tuban is as many as 385 people and the sample is all mothers who suffered the old partus as many as 34 people. Sampling technique using saturated sampling. The results of the study showed that of 34 mothers in RSUD Dr. R. Koesma Tuban, Most of the mothers have long labor> 18 hours (50%). All maternal mothers experience abnormalities (100%). Almost all mothers do not have fetal abnormalities (91%) .The entire mothers do not have birth abnormalities (100%). From this research, it can be concluded that power factor is the most dominant partus cause. So at the time of examination of pregnant women (ANC) nutritional needs of pregnant women should be considered in order to suppress the number of old partus events